Fatigue crack propagation of aeronautic AA7050-T7451 and AA2050-T84 aluminum alloys in air and saline environments - Cavalcante, T. R.F.; Pereira, G. S.; Koga, G. Y.; Bolfarini, C.; Bose Filho, W. W.; Avila, J. A. [UNESP] (Elsevier, 2022)
AA7050-T7451 aluminum alloy is one of the most used material in aeronautical applications due to its high strength/density ratio and good fatigue resistance. More recently the AA2050-T84 alloy was introduced due to its reduced density and comparable static mechanical properties. However, fatigue crack propagation properties in corrosive environments are yet to be documented. In this paper fatigue crack propagation was evaluated in saline (3.5 wt% NaCl solution) and air environments. The AA2050-T84 alloy presented a better fatigue performance both in air and aqueous saline environments. Its superior performance was ascribed to non-homogeneous deformation and higher corrosion resistance. These results show the AA2050-T84 alloy as a potential candidate to replace AA7050-T7451 alloy in aeronautical components subjected to fatigue in corrosive environments.
Keywords: AA2050 alloy; AA7050 alloy; Aeronautical materials; Corrosion fatigue; Fatigue